2006
DOI: 10.1139/y06-059
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-independent tacrine-induced relaxation of rat gastric corpus smooth muscles

Abstract: Tacrine, a non-competitive reversible acetylcholinesterase and butyrylcholineserase inhibitor, caused a concentration-dependent tonic contraction of gastric smooth muscle preparations in the concentration range 1 x 10(-7) mol/L - 1 x 10(-5) mol/L, whereas concentrations higher than 2 x 10(-5) mol/L induced a biphasic effect; a short-time contraction was followed by a prolonged relaxation. To shed some light on the mechanism underlying this untypical relaxation, the amplitude of mechanical reactions caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, the tacrine-treated animals showed some specific reactions, namely, fornical and caecal relaxation, antral contraction, and a lack of statistically significant peristaltic activity. The combination of tacrin-induced non-anticholinesterase and noncholinergic tonic relaxation and the inhibition of the phasic mechanical activity [30] combined with the contractile effects of acummulated actylcholine can account for the changes that we observed. In addition, there are likely variations in the thresholds for these acetylcholinesterase-indepent effects in different areas of the GI tract [31].…”
Section: * Comparison Between Experimental Group and Control † Comparmentioning
confidence: 65%
“…However, the tacrine-treated animals showed some specific reactions, namely, fornical and caecal relaxation, antral contraction, and a lack of statistically significant peristaltic activity. The combination of tacrin-induced non-anticholinesterase and noncholinergic tonic relaxation and the inhibition of the phasic mechanical activity [30] combined with the contractile effects of acummulated actylcholine can account for the changes that we observed. In addition, there are likely variations in the thresholds for these acetylcholinesterase-indepent effects in different areas of the GI tract [31].…”
Section: * Comparison Between Experimental Group and Control † Comparmentioning
confidence: 65%
“…Our previous studies have shown that the relaxation effect of tacrine at concentrations higher than 2×10 -5 mol/l had no related with modulation of cytosolic Са 2+ level of treated SM cells but probably with desensitization of the SM contractile apparatus to Са 2+ [14]. The sensitization (desensitization) states of the contractile apparatus and the resulting SM contraction (relaxation) are usually a function of the ratio between the activity of myosin light-chain kinase (MLCK) and myosin light chain phosphatase (MLCP).…”
Section: Discussionmentioning
confidence: 87%
“…Drugs that inhibit muscarinic receptors on gastrointestinal smooth muscles and nicotinic receptors on enteric nerve cells do not influence the amplitude of tacrine-induced relaxation [13]. This relaxation was not affected by preliminary treatments of muscle strips with tetrodotoxin (ТТХ), a nerve action potentials blocker, potassium channel blockers (charybdotoxin, apamin, tetraethylammonium, and 4-aminopyridine) [14], and Ca 2+ antagonists [15]. Therefore, this relaxing effect of tacrine is Ca 2+ -independent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous investigations have shown that tacrine exerts some of its non-anticholinesterase effects on gastric SMs by increasing the cAMP level, stimulating adenylate cyclase (AC) and activating the intracellular pathway: сАМР -protein kinase А (РKА) -myosin light chain protein kinase (MLCPK) -the contractile apparatus of SMs [11] The effect of triggering this mechanism occurs as a Са 2+ -independent SM relaxation [12] that dominates the behavior of SM preparations at concentrations higher than 1×10 -5 mol/l. сАМР and РKА, respectively, are important signal molecules in the body of humans and animals, which are involved in many physiological and pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%